Valoración de empresas como herramienta para mejorar los niveles de rentabilidad en las empresas de asistencia médica en el cantón Quito - Arcos Paguay, Myrian Elena (2017)
Abstract The following document aims to analyze the valuation of companies as tools to improve levels of profitability in health care companies located in the canton Quito. For the purpose of the following work will explore sources of information that will be obtained through surveys and bibliographic information from reliable sources. Primarily, information will be obtained from bibliographic references such as articles, books and theses related to the 3 subject and the survey will continue to be carried out and applied, which will have as main guide the general and specific objectives of what is the valuation of companies and the levels of profitability of the Assistance companies today and the relationship that the two have, the survey will consist of 20 questions that will help to collect, process and inquire the information already mentioned, with which it will later be used to make a descriptive analysis of which is the best Tool to improve the profitability of companies that are destined for medical care in the canton Quito, which will later be able to implement the best tool in these companies, thus increasing their profitability. As a result of the research the Goodwill Mixed Method, would seem to be the most appropriate for this type of company, so the Intangible Assent can be estimated in money to the extent that the future benefits of its prestige and good name can be measured. Entities use resources, or incur liabilities, in the acquisition, development, maintenance or improvement of intangible resources such as scientific or technological knowledge, the design and implementation of new processes or new systems, licenses or concessions, intellectual property, commercial knowledge or trademarks; not forgetting that indirectly the health care companies apply the Cash Flow Method. Is the one that best suits the needs of the sector. In addition, it is possible to establish the importance of the application of revaluation model, as an option that can be exercised by the local entity freely, provided that the requirements established by the valuation standard that regulates it are met, the revaluation or part of the Balance Method or result and that all companies should consider, as it helps to reduce the costs that affect the future 4 income statement, take more convenient criteria according to the tax regulations and fair value of the Financial Statements.